1984
DOI: 10.3382/ps.0630607
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Abdominal Fat, Body Weight, and Carcass Weight in a Female Broiler Line

Abstract: Pedigreed matings in a commercial purebred female broiler selection line produced 311 males and 341 females, which were slaughtered at 50 days of age. Coefficients of variation of abdominal fat weights were higher than live and carcass weights. The coefficient of variation was reduced when abdominal fat was regressed on live weight or when percentage of live or carcass weight was used. Leaf fat was approximately two-thirds and gizzard fat was approximately one-third of the total abdominal fat. Heritabilities f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
1
3

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 5 publications
7
16
1
3
Order By: Relevance
“…The estimate of .41 to .52 for the heritability of the relative amount of abdominal fat in this study agrees well with estimates of Becker et al (1984), Ricard (1975), Leclercq et al (1980), and .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The estimate of .41 to .52 for the heritability of the relative amount of abdominal fat in this study agrees well with estimates of Becker et al (1984), Ricard (1975), Leclercq et al (1980), and .…”
Section: Discussionsupporting
confidence: 86%
“…The large variation in the relative amount of abdominal fat, combined with a heritability Coefficients of variation of 20 to 30% for the amount of abdominal fat, both absolute and relative to body weight, were found in nearly all cases in which variability in amount of abdominal fat was examined (Becker et al, 1984, Leenstra, 1984.…”
Section: Discussionmentioning
confidence: 97%
“…al, 1980). The genetic relationship between growth rate and fatness is large and positive in broiler chickens (Becker et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal and whole carcass fat were shown to have moderate to high heritability and to be positively correlated, both genetically and phenotypically, with body weight (Siegel, 1984). Becker et al (1984) concluded that abdominal fat could be reduced by selection but with a correlated reduction in body weight.…”
Section: Introductionmentioning
confidence: 97%